2002
DOI: 10.1046/j.1432-1327.2002.02824.x
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and expression in Pichia pastoris of a blue mussel (Mytilus edulis) β‐mannanase gene

Abstract: Using PCR, cloning and sequencing techniques, a 1.1-kb complementary DNA fragment encoding for a b-mannanase (mannan endo-1,4-b-mannosidase, EC 3.2.1.78) has been identified in the digestive gland of blue mussel, Mytilus edulis. The cDNA sequence shows significant sequence identity to several b-mannanases in glycoside hydrolase family 5. The b-mannanase gene has been isolated and sequenced from gill tissue of blue mussel and contains five introns. The b-mannanase has been expressed extracellularly in Pichia pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
33
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 35 publications
2
33
1
Order By: Relevance
“…In each case, the GH-A (␤/␣) 8 barrels were predominant in the 3D-jury consensus results with the scores ranging from 74 to 198. The scores were well above the benchmark of 50, suggesting that all GH113 members folded into a GH-A (␤/␣) 8 barrel. Sequence alignment between AaManA and the other GH113 members showed that the catalytic residues (indicated by the diamond and triangle in Fig.…”
Section: Overall Structure Comparison With Other Glycoside Hydrolases-mentioning
confidence: 88%
See 4 more Smart Citations
“…In each case, the GH-A (␤/␣) 8 barrels were predominant in the 3D-jury consensus results with the scores ranging from 74 to 198. The scores were well above the benchmark of 50, suggesting that all GH113 members folded into a GH-A (␤/␣) 8 barrel. Sequence alignment between AaManA and the other GH113 members showed that the catalytic residues (indicated by the diamond and triangle in Fig.…”
Section: Overall Structure Comparison With Other Glycoside Hydrolases-mentioning
confidence: 88%
“…As shown in Fig. 5A, AaManA folds into a typical (␤/␣) 8 -barrel. On the top of the barrel, AaManA features a groove (indicated by a red arrow in Fig.…”
Section: Characterization Of the Gene Cluster Containing Aamana-mentioning
confidence: 92%
See 3 more Smart Citations